Killer Immunoglobulin-Like Receptor Profiles Are not Associated with Risk of Amoxicillin-Clavulanate–Induced Liver Injury in Spanish Patients - Stephens, Camilla; Moreno-Casares, Antonia; López-Nevot, Miguel-Ángel; García-Cortés, Miren; Medina-Cáliz, Inmaculada; Hallal, Hacibe; Soriano, German; Roman, Eva; Ruiz-Cabello, Francisco; Romero-Gomez, Manuel; Lucena, M. Isabel; Andrade, Raúl J. (Frontiers in Pharmacology, 2016)
Natural killer cells are an integral part of the immune system and represent a large proportion of the lymphocyte population in the liver. The activity of these cells is regulated by various cell surface receptors, such as killer Ig-like receptors (KIR) that bind to human leukocyte antigen (HLA) class I ligands on the target cell. The composition of KIR receptors has been suggested to influence the development of specific diseases, in particularly autoimmune diseases, cancer and reproductive diseases. The role played in idiosyncratic drug-induced liver injury (DILI) is currently unknown. In this study we examined KIR gene profiles and HLA class I polymorphisms in amoxicillin-clavulanate (AC) DILI patients in search for potential risk associations. 102 AC DILI patients and 226 controls were genotyped for the presence or absence of 16 KIR loci, including the two pseudogenes 2DP1 and 3DP1. No significant differences were found in the distribution of individual KIRs between patients and controls, which were comparable to previously reported KIR data from ethnically similar cohorts. 21.6% and 21.2% of the patients and controls, respectively, were homozygous haplotype A carriers, while 78.4% and 78.8%, respectively, contained at least one B haplotype (Bx). The genotypes translated into 27 (AC DILI) and 46 (controls) different gene profiles, with 19 being present in both groups. The most frequent Bx gene profile containing 2DS2, 2DL2, 2DL3, 2DP1, 2DL1, 3DL1, 2DS4, 3DL2, 3DL3, 2DL4 and 3PD1 was present in 16% of the DILI patients and 14% of the controls. The distribution of HLA class I epitopes did not differ significantly between AC DILI patients and controls. The most frequent receptor-ligand combinations in the DILI patients were 2DL3 + epitope C1 (67%) and 3DL1 + Bw4 motif (67%), while 2DL1 + epitope C2 (69%) and 3DL1 + Bw4 motif (69%) predominated in the controls. This is to our knowledge the first analysis of KIR receptor-HLA ligand associations in DILI, although our findings do not support evidence of these genetic variations playing a major role in AC DILI development.